The Effects of Oral Narrative Intervention on the Personal Narratives of Children with ASD and Severe Language Impairment: A Pilot Study. Issue 5 (3rd September 2019) - Favot, Kate; Carter, Mark; Stephenson, Jennifer
Abstract: The purpose of this pilot study was to examine and refine an oral narrative intervention addressing personal narratives of children with autism spectrum disorder (ASD) and severe language impairment. A multiple baseline across participants design investigated the effect of the intervention on the macrostructure of personal narratives. Three five–six year olds participated in a 1:1 intervention that targeted the where, who with, what and feelings of personal narrative. Intervention included macrostructure icons, pictures, modelling and participants telling the entire narrative. Participants received training with two or three narratives each session. The intervention was effective for all three participants. Two participants showed evidence of maintenance and generalisation across settings. The results show that children with autism and severe language impairment may benefit from oral narrative intervention targeting the macrostructure of personal narrative. These results are consistent with previous findings. Areas for future research include investigation of generalisation across people.